2020
DOI: 10.1126/science.abb9519
|View full text |Cite
|
Sign up to set email alerts
|

Seismic ocean thermometry

Abstract: More than 90% of the energy trapped on Earth by increasingly abundant greenhouse gases is absorbed by the ocean. Monitoring the resulting ocean warming remains a challenging sampling problem. To complement existing point measurements, we introduce a method that infers basin-scale deep-ocean temperature changes from the travel times of sound waves that are generated by repeating earthquakes. A first implementation of this seismic ocean thermometry constrains temperature anomalies averaged across a 3000-kilomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 58 publications
4
80
1
Order By: Relevance
“…They can be excited by earthquakes through the conversion of elastic energy into acoustic waves at the solid-liquid interface (e.g., Talandier and Okal, 1998;Park et al, 2001). T waves recorded on seismograph and hydrophone networks have been used in a large number of studies including: small earthquake 11 detection and retrieval of seismic source properties in marine environments (Okal and Talandier, 1986), detection of volcanic activity (Talandier and Okal, 1987), underwater landslides (Fryer et al, 2004), or global climate change (Wu et al, 2020). T phases are useful to locate seismicity at mid-oceanic ridges because, due to the low attenuation at the SOFAR channel, they can transmit energy from relatively small sources over large epicentral distances.…”
Section: Hydroacoustic Phasesmentioning
confidence: 99%
“…They can be excited by earthquakes through the conversion of elastic energy into acoustic waves at the solid-liquid interface (e.g., Talandier and Okal, 1998;Park et al, 2001). T waves recorded on seismograph and hydrophone networks have been used in a large number of studies including: small earthquake 11 detection and retrieval of seismic source properties in marine environments (Okal and Talandier, 1986), detection of volcanic activity (Talandier and Okal, 1987), underwater landslides (Fryer et al, 2004), or global climate change (Wu et al, 2020). T phases are useful to locate seismicity at mid-oceanic ridges because, due to the low attenuation at the SOFAR channel, they can transmit energy from relatively small sources over large epicentral distances.…”
Section: Hydroacoustic Phasesmentioning
confidence: 99%
“…Studies based on observations have confirmed the warming of ocean waters since the last decades of the 20th century (Johnson & Lyman, 2020; Rhein et al., 2013; Strass et al., 2020; Wu et al., 2020). The rate of warming is mostly observed in the upper 2,000 m (Johnson & Lyman, 2020; Wu et al., 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Repeating earthquakes (repeaters) are events that recurrently rupture the same fault patch with the same focal mechanisms, often characterized by nearly identical waveforms (Abercrombie et al., 2020; Gao & Kao, 2020; Hatch et al., 2020; Sheng et al., 2021; Uchida & Bürgmann, 2019). These events are of great importance in many aspects of geophysics, such as monitoring subtle temporal changes of crustal properties (e.g., Pacheco et al., 2017; Poupinet et al., 1984; Sawazaki et al., 2015; Schaff & Beroza, 2004) and oceanic temperature (Wu et al., 2020), estimating fault creep (e.g., Materna et al., 2018; Matsubara et al., 2005; Nadeau & Johnson, 1998; Uchida et al., 2003, 2006; Yu, 2013), investigating inner core rotation (e.g., A. Li & Richards, 2003; Tkalčić et al., 2013; Zhang et al., 2005, 2008), evaluating the precision of earthquake locations (e.g., Jiang et al., 2014; A. Li & Richards, 2003; Meier et al., 2004; Schaff & Richards, 2011), and providing insights into the nucleation process of earthquakes (Huang & Meng, 2018; Kato & Nakagawa, 2014; Kato et al., 2012; Meng et al., 2015) and landslides (Yamada et al., 2016).…”
Section: Introductionmentioning
confidence: 99%